Modeling of table grape soluble solids content, titratable acidity and pH prediction during storage based on Vis-NIR spectroscopy - He, Ke; Su, Yuan; He, Lei; Hu, Can; Xing, Jianfei; Alisher, Naimov (Frontiers in Plant Science, 2025)
IntroductionThe soluble solids content (SSC), titratable acidity (TA), and pH are key indicators for evaluating the quality of table grapes during storage. Conventional detection methods are typically destructive and time-consuming. To address this limitation, visible-near infrared (Vis-NIR) spectroscopy was employed in this study to enable rapid and non-destructive quality assessment of fresh table grapes throughout the storage period.MethodsSeedless White table grape samples were analyzed within the 200–1100 nm spectral range, and calibration models for key quality parameters (SSC, TA, and pH) were established. Three machine learning algorithms, partial least squares regression (PLSR), support vector machine (SVM), and extreme learning machine (ELM), were employed to develop spectral prediction models based on characteristic wavelengths selected using different feature extraction strategies, including the successive projection algorithm (SPA), uninformative variable elimination (UVE), and competitive adaptive reweighted sampling (CARS).ResultsThe results demonstrate that the SNV-CARS-SVM models achieved excellent performance in predicting SSC with a root mean square errors (RMSEP) of 0.673, a coefficient of determination for the prediction data set (Rp) of 0.928 and an RPD of 3.311. Similarly, the SNV-SPA-SVM models exhibited excellent predictive accuracy for TA, yielding an RMSEP of 0.553, an Rp of 0.873, and an RPD of 2.662. Good performances were achieved with Rp of 0.758 and RMSEP of 0.113 with the SNV-CARS-PLSR model for pH.DiscussionThis study, for the first time, utilized Vis-NIR spectroscopy to achieve the simultaneous and rapid determination of multiple quality attributes in table grapes, providing a novel and efficient strategy for real-time and non-destructive quality evaluation during storage. The proposed approach showed considerable potential for rapid quality assessment and postharvest management of grapes. Future research will focus on expanding the diversity of grape cultivars and investigating various storage conditions to improve the robustness and transferability of the predictive model, thereby promoting the industrial validation and practical application of Vis-NIR spectroscopy in fruit quality monitoring.